2022
DOI: 10.1177/14767503221137851
|View full text |Cite
|
Sign up to set email alerts
|

Images and indicators: mixing participatory methods to build inclusive rigour

Abstract: Participatory methods seek to counter the extractive nature of mainstream research methods by putting control into the hands of research subjects. But participation itself does not guarantee against extraction. There is a tension between the desire for researcher-control and the prerogative of community action in participatory methods. How can researchers committed to participation manage this tension? In this paper, we draw on the concepts of “collaborative” and “action-oriented” participatory research to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…A key motivation for combining the methods was to enhance participation, build community ownership and encourage action around EPI indicators (Fairey et al, 2022). Everyday Peace Indicators managed the design and bricolage of the EPI and photovoice components, thus decisions were based mostly on their methodological understanding and institutional priorities, and continues to explore the results of this pilot for bricolage application in their organisation.…”
Section: Mali Vestibule De La Paixmentioning
confidence: 99%
See 2 more Smart Citations
“…A key motivation for combining the methods was to enhance participation, build community ownership and encourage action around EPI indicators (Fairey et al, 2022). Everyday Peace Indicators managed the design and bricolage of the EPI and photovoice components, thus decisions were based mostly on their methodological understanding and institutional priorities, and continues to explore the results of this pilot for bricolage application in their organisation.…”
Section: Mali Vestibule De La Paixmentioning
confidence: 99%
“…Evaluative research conducted around the photovoice process in the first two communities revealed that the process supported healing, enabled intergenerational dialogue, built territorial identity and catalysed community peace actions (Fairey et al, 2022). Crucially, these community impacts emerged as the photovoice process built on existing community strengths and priorities as identified in the participatory indicator process.…”
Section: Case Studies Of Inclusive Rigour In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…This is based on the premise that local communities are best placed to identify changes, needs, and priorities in their own circumstances, either alone or in conversation with experts. Indicator generation is sometimes accompanied by longitudinal surveys or qualitative assessments such as interviews or more participatory methods such as photovoice (Fairey, Firchow, and Dixon 2022).…”
Section: Understanding and Measuring Justicementioning
confidence: 99%
“…In terms of practice we learn of encounters with animals who appear at our river encounters, with reflections on the veracity claims we are making. Fairey et al (2022) acknowledge the elemental need to work with stakeholders and they also problematize what can appear as a simple cure all. They point out that the sensemaking that drives participation can be extractive, a Modernist old wine in new bottles that carries over the extractive nature of mainstream research methods.…”
Section: Introduction To This Issuementioning
confidence: 99%